Σύλληψη αλλοδαπών για ναρκωτικά στη Χίο (HellenicCoastguard, 2022)
: Βασίλειο, Βασίλειο, Βασίλειο... Βασίλειο, Βασίλειο, Βασίλειο, Βασίλειο... Βασίλειο, Βασίλειο, Βασίλειο... Βασίλειο, Βασίλειο, Βασίλειο... Βασίλειο, Βασίλειο, Βασίλειο...